TOPICAL ASPECTS OF COMBINED COMBAT THERMOMECHANICAL INJURIES - Korol, S.O.; Chelishvili, A.L.; Palii, I.P.; Zhovtonozhko, O.I.; Musenko, O.Ya.; Svystak, N.V. (World of Medicine and Biology, 2023)
Severe mechanical injuries and large and deep burns lead to burn and wound shock, which is more severe than in isolated mechanical wounds and burns. The key syndrome in the pathogenesis of shock named hemocirculation disorders syndrome is formed as a result of blood and plasma loss, including losses caused by burn wounds. In medical evacuation of the wounded persons with severe and extremely severe combined injuries, there is a tendency to accelerate the transportation of the wounded persons to the next stage as fast as possible, and sometimes the severity of injuries is not taken into account, which leads to deterioration in the condition of the wounded persons. There was a comparative integrated clinical examination of 183 injured persons, who were divided into 3 groups. Group 1 consisted of 71 wounded persons with combat extremity injuries, Group 2 consisted of 61 persons with minor injuries, and Group 3 consisted of 57 persons with severe and extremely severe injuries.
Keywords: combined combat thermomechanical injury; wound shock; shock